2022
DOI: 10.1371/journal.pone.0277895
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a winter sentinel surveillance program of notifiable respiratory viruses in Queensland

Abstract: Background With the reduction in access to polymerase chain reaction (PCR) testing and changes in testing guidelines in Australia, a reduced number of people are seeking testing for coronavirus disease (COVID-19), limiting the opportunity to monitor disease transmission. Knowledge of community transmission of COVID-19 and other respiratory viruses is essential to better predict subsequent surges in cases during the pandemic to alert health services, protect vulnerable populations and enhance public health meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Sentinel screening tests in asymptomatic populations are effective in preventing infection [19,20,39] . Their implementation, especially in the era of highly cryptic infections like Omicron-related variants, should be considered owing to their low facility burden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sentinel screening tests in asymptomatic populations are effective in preventing infection [19,20,39] . Their implementation, especially in the era of highly cryptic infections like Omicron-related variants, should be considered owing to their low facility burden.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other countries, Japan has been severely affected by the coronavirus disease 2019 (COVID- 19) pandemic. As of May 10, 2023, the Japanese National Epidemiological Surveillance of Infectious Diseases (NESID) reported 33,793,429 cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, with a low number of related deaths at 74,654 [1] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that while self-collected nasal swabs are not as accurate as clinician-collected swabs, the convenience outweighs the reduced sensitivity. [30][31][32][33] While this programme required fewer staffing resources than the previous door-knocking prevalence programme Open access conducted in Gold Coast, 24 significant staff time was required for the daily messaging, creation of personalised swab packs, dropping packs to workplaces, picking up swabs from workplaces and delivery to the laboratory, in addition to the data analysis and additional pressure on the laboratory staff. Funding was also required for the consumables used during the programme.…”
Section: Discussionmentioning
confidence: 99%
“…This longitudinal testing-based sentinel surveillance programme based on the protocol by Ginige et al 24 was designed to detect winter respiratory viruses notifiable under the Public Health Act 2005 (Queensland). 25 All participants were tested for SARS-CoV-2 and symptomatic participants were also tested for influenza A and B, and RSV.…”
Section: Methodsmentioning
confidence: 99%